Ta'lim Muta'alim Fasal 9 Tentang Kasih Sayang Dan Nasihat - Adawiyyah Filantrophi; Martoyo Martoyo (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The book of Ta “limul Muta'allim covers various topics related to learning, including learning strategies, principles, objectives, and methodologies. The main purpose of learning techniques, learning principles, learning strategies, and so on is to guide a person towards morality and akhlaqul karimah. Akhlakul is any praiseworthy or good action that is embedded in a person's soul and eventually develops into a positive habit, the human soul, which then turns into a virtue. The Rationale Behind Morality. The purpose of morality is for humans to behave well towards God and other living beings so as to raise their status in the eyes of these beings and ensure that God is higher than others and achieve a higher status than other creatures, receive the pleasure of God, and ultimately experience worldly and ukhrawi happiness.